REFORMASI ADMINISTRASI DENGAN PENDEKATAN “SYSTEMS THINKING” MENGKONSTRUKSI BIROKRASI DALAM MENGATASI KOMPLEKSITAS PERMASALAHAN UNTUK SUATU PERUBAHAN - Endang Wirjatmi Trilestari (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
There has been no single perfect public administration system in the world. However, public administration has always impediments in performing its chores. When the hurdles arise and disrupt the equilibrium of the country, it indicates that there must be a demand for an administrative reform. The need for bureaucratic reform evolves due to unnaturally changing administration process.In addition to public bureaucracy, administrative reform should also take into account social, political and economic factors significantly influential to the reform cycle. Administrative reform movement may be conducted through several approaches; one of those is through system thinking approach. Through this approach, it is expected that bureaucracy will transform itself into the one which is creative, innovative, productive, professional, and accountable. Further more, bureaucracy is also expected to be able to reflect on and learn from its pastshortcomings.